Fiber ball white matter modeling in focal epilepsy. Issue 8 (19th February 2021) - Bryant, Lorna; McKinnon, Emilie T.; Taylor, James A.; Jensen, Jens H.; Bonilha, Leonardo; de Bezenac, Christophe; Kreilkamp, Barbara A. K.; Adan, Guleed; Wieshmann, Udo C.; Biswas, Shubhabrata; Marson, Anthony G.; Keller, Simon S.
Abstract: Multicompartment diffusion magnetic resonance imaging (MRI) approaches are increasingly being applied to estimate intra‐axonal and extra‐axonal diffusion characteristics in the human brain. Fiber ball imaging (FBI) and its extension fiber ball white matter modeling (FBWM) are such recently described multicompartment approaches. However, these particular approaches have yet to be applied in clinical cohorts. The modeling of several diffusion parameters with interpretable biological meaning may offer the development of new, noninvasive biomarkers of pharmacoresistance in epilepsy. In the present study, we used FBI and FBWM to evaluate intra‐axonal and extra‐axonal diffusion properties of white matter tracts in patients with longstanding focal epilepsy. FBI/FBWM diffusion parameters were calculated along the length of 50 white matter tract bundles and statistically compared between patients with refractory epilepsy, nonrefractory epilepsy and controls. We report that patients with chronic epilepsy had a widespread distribution of extra‐axonal diffusivity relative to controls, particularly in circumscribed regions along white matter tracts projecting to cerebral cortex from thalamic, striatal, brainstem, and peduncular regions. Patients with refractory epilepsy had significantly greater markers of extra‐axonal diffusivity compared to those with nonrefractory epilepsy. The extra‐axonal diffusivity alterations in patients with epilepsy observed in the present study could be markers of neuroinflammatory processes or a reflection of reduced axonal density, both of which have been histologically demonstrated in focal epilepsy. FBI is a clinically feasible MRI approach that provides the basis for more interpretive conclusions about the microstructural environment of the brain and may represent a unique biomarker of pharmacoresistance in epilepsy. Abstract : Bryant et al. used fiber ball imaging to measure intra‐axonal and extra‐axonal white matter diffusion in patients with longstanding focal epilepsy. It is reported that extra‐axonal diffusion is different between patients with refractory and nonrefractory epilepsy and may represent a novel imaging biomarker of pharmacoresistance.